(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
During the training of students at the medical faculty, future doctors should develop professional thinking based on the principles of evidence-based medicine. To understand to what extent medical students are inclined to be guided by these principles when choosing treatment, a survey was conducted, including a question about the rationality of using various traditional medicine for the treatment of oncological diseases.